Who is government? [large type] : the untold story of public service - Lewis, Michael (Michael M.); Cep, Casey N.; Eggers, Dave; Lanchester, John; Brooks, Geraldine; Vowell, Sarah, 1969-; Bell, W. Kamau; Lewis, Michael (Michael M.) (Thorndike Press large print nonfiction series., 2025)
"The government is a vast, complex system made up of people, mostly unrecognized and uncelebrated, doing work that can be deeply consequential and beneficial to everyone. Michael Lewis invited his favorite writers to find someone doing an interesting job for the government and write about them. Whether they're digitizing archives, chasing down cybercriminals, or discovering new planets, these public servants are committed to their work and universally reluctant to take credit. The vivid profiles in Who Is Government? show how the essential business of government makes our lives possible and how much it matters"--